2019
DOI: 10.1371/journal.pntd.0007405
|View full text |Cite
|
Sign up to set email alerts
|

Ticks and serosurvey of anti-Rickettsia spp. antibodies in wild boars (Sus scrofa), hunting dogs and hunters of Brazil

Abstract: Background Rickettsia bacteria are responsible for diseases in humans and animals around the world, however few details are available regarding its ecology and circulation among wild animals and human populations at high transmission risk in Brazil. The aim of this study was to investigate the occurrence of ticks and Rickettsia spp. in wild boars, corresponding hunting dogs and hunters. Methods Serum samples and ticks were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
40
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 51 publications
2
40
0
2
Order By: Relevance
“…These findings suggest that in rural and peri-urban contexts (i.e., wooded landscapes and hunting areas), hikers/wild boar hunters and hunting dogs may be exposed to D. marginatus , which is commonly retrieved infesting humans and dogs in southern Italy (Otranto et al, 2014). Accordingly, a seroepidemiological survey conducted in Brazil reports that 14.1% of hunting dogs and 14.7% of hunters were exposed to at least one Rickettsia species (Kmetiuk et al, 2019). Again, the period in which the incidence of R. slovaca infection in humans is higher (Raoult et al, 2002;Parola et al 2009) overlaps the boar hunting season (i.e., October to December), suggesting a direct relationship between the risk of Rickettsia spp.…”
Section: Discussionmentioning
confidence: 95%
“…These findings suggest that in rural and peri-urban contexts (i.e., wooded landscapes and hunting areas), hikers/wild boar hunters and hunting dogs may be exposed to D. marginatus , which is commonly retrieved infesting humans and dogs in southern Italy (Otranto et al, 2014). Accordingly, a seroepidemiological survey conducted in Brazil reports that 14.1% of hunting dogs and 14.7% of hunters were exposed to at least one Rickettsia species (Kmetiuk et al, 2019). Again, the period in which the incidence of R. slovaca infection in humans is higher (Raoult et al, 2002;Parola et al 2009) overlaps the boar hunting season (i.e., October to December), suggesting a direct relationship between the risk of Rickettsia spp.…”
Section: Discussionmentioning
confidence: 95%
“…Research groups in Brazil have also been applying One Health as a practical tool to solve problems such as zoonoses in different populations and their contact animals, taking advantage of the SUS, which allows comprehensive human-animal sampling. In such scenarios, wild boars, hunting dogs, and hunters have been surveyed in Brazil for vector-borne, waterborne, and foodborne diseases, for the first time worldwide (21). Moreover, One Health research and outreach community projects with community leaders toward Brazilian social classes vulnerability have provided interesting results in animal hoarders, homeless, incarcerated, indigenous, slum, low-income, and traditional island populations in their environments (22)(23)(24)(25).…”
Section: One Health In Brazilmentioning
confidence: 99%
“…Although a concomitant study in Colombia sampling 58 collared peccaries and 15 wild boars, showed no positive cases (Montenegro et al 2018), De Castro et al (2014 detected PRV by PCR in spleen samples of all 10 collared peccaries and all three white lipped peccaries sampled from central-western and northern Brazil, using primers designed against swine pseudorabies variant. Such overlap has been confirmed in the Atlantic Forest biome by wild boars infested with the adult and nymph stages of ticks (Amblyomma brasiliense), which use collared peccaries as primary hosts in humid forests (Kmetiuk et al 2019). In the Cerrado biome, peccary habitat destruction and fragmentation has been related to wild boar occurrence (Silveira and Pacheco 2018).…”
mentioning
confidence: 89%
“…In Brazil, wild boars have been classified as an exotic invasive species, originated from Eurasian wild boars and their hybrids, and nationwide hunting is officially permitted as a strategy for population control and eradication (Kmetiuk et al 2019). Due to their highly adaptive capacity, wild boars have invaded all six Brazilian biomes, including the Atlantic Forest and Cerrado of central-western, southwestern, and southern Brazil (Kmetiuk et al 2019). Although PRV infection is reportedly established in wild boars elsewhere, no study has been conducted in free-ranging wild boars of Brazil.…”
mentioning
confidence: 99%
See 1 more Smart Citation